Early and late Biliary Complications of Laparoscopic Cholecystectomy in Acute Cholecystitis - Khattab, Omar Salem (AL-Kindy College Medical Journal, 2011)
Background: Laparoscopic cholecystectomyhas become the standard of care for theelective management of cholelithiasis. Littleinformation exists, however, regarding theappropriateness of this procedure in the settingof acute symptomatology.Objective: This study was designed toevaluate the outcome of laparoscopiccholecystectomy in acute and severe acutecholecystitis based on early and late biliarycomplications, their incidence andmanagement, and conversion rates to opensurgery.Methods: A prospective study done betweenApril 2007 and November 2010, in thedepartment of general surgery, medical cityteaching hospital, Baghdad. Includes patientswith acute cholecystitis admitted forlaparoscopic cholecystectomy; they weredivided into two groups, (group 1) includingpatients with acute cholecystitis; (group 2)including patients with severe acutecholecystitis.Results: 306 patients were admitted forlaparoscopic cholecystectomy, 71 (23.2%) ofthem with acute cholecystitis and was involvedin this study; they were divided into twogroups, (group 1) patients with acutecholecystitis 61(85.9%), (group 2) patientswith severe acute cholecystitis 10 (14%);including gangrenous gallbladder 3(30%), andempyematous gallbladder 7(70%). Patients ingroup 2 were significantly older than in group1. Female sex was more significant in group 1,while male sex was more significant in group.There was no procedure related mortality.Conclusion: laparoscopic cholecystectomyfor acute cholecystitis is safe and associatedwith a low morbidity, mortality, and a lowconversion rate.